Bisnis dan Politik: Studi Kasus Ketidaksetaraan Akses Air di India - Tsania Chairani (Journal of International Relations, 2023)
Water is a source of life for all living things, one of which is for humans. The supply of clean water that is safe for consumption is currently only available for 3 percent of the total of 70 percent of the earth’s water area. India as a country with a large population, has a high chance of experiencing a water crisis. This is evidenced by the low quality of India’s water, the existence of unequal access of it and the ineffectiveness of government cooperation with foreign companies recruited to manage water in India. Through this research, the author try to explain the relationship between the government’s cooperation with foreign companies which causes the existence of unequal access to water in India. By using the theory of Marxism which views world politics as an exploitative and conflictual desert between the bourgeoisie and the proletarian class as well as the theory of Monopoly Advantage which discusses the importance of monopoly over a foreign company in another country, this research argues that cooperation by the government and foreign companies has resulted in the exploitation of water allotment for people in rural areas and led to unequal access to water in India.